Inhibition of IP3 (Inositol 1,4,5-Trisphosphate) Receptors Retards SARS-CoV-2-Induced Endothelial von Willebrand Factor Secretion and Thrombosis - Yu, Xin-yi; Jia, Xin-yu; Wang, Ting-yu; Zhang, Yan-hong; Song, Hao; Li, Kan; Chen, Zhuo-zheng; Zhu, Yi; Yao, Liu (Thrombosis and Haemostasis, 2025)
Patients with coronavirus disease 2019 (COVID-19) are at high risk of developing a hypercoagulable state and thrombosis. The von Willebrand factor (vWF) produced by endothelial cells (ECs) is a critical thrombosis regulator. We previously found that cytoskeleton-associated protein 4 (CKAP4) is a novel receptor for the spike protein of severe acute respiratory syndrome coronavirus-2 and is involved in COVID-19-associated coagulopathy. However, the underlying mechanism involved remains unclear. This study aimed to explore the signaling pathways involved in spike protein-CKAP4-induced vWF secretion and thrombosis. Treatment of ECs with the spike protein significantly induced vWF secretion, coagulation factor VIII (FVIII)–vWF binding, and platelet adhesion to ECs, which were blocked by the selective intracellular calcium chelator, BAPTA-AM. Furthermore, using several calcium channel-blocking drugs and small-molecule inhibitors, we found that calcium released from the endoplasmic reticulum (ER) is involved in this process. IP3 (inositol 1,4,5-trisphosphate) receptors (IP3Rs) inhibition ameliorated spike protein-induced vWF secretion, FVIII–vWF binding affinity, and platelet adhesion to ECs. Specifically, the knockdown of IP3R1, a crucial type of IP3Rs, reversed spike protein-induced endothelial vWF secretion, and the procoagulant state. Moreover, KT-362, an investigational and clinically relevant antihypertensive drug targeting IP3Rs-mediated calcium release, repressed spike protein-induced endothelial vWF secretion. Conversely, the IP3Rs agonist promoted endothelial vWF secretion, which was not affected by CKAP4 knockdown. In vivo treatment of endothelial-specific human CKAP4 overexpression mice with KT-362 retarded spike protein-induced vWF secretion and thrombosis. Thus, IP3Rs mediated calcium release from the ER and contributed to spike protein-induced vWF secretion and thrombosis, making them potential therapeutic targets for COVID-19-associated coagulopathy.
Keywords: spike protein; endothelium; von Willebrand factor; IP3 (inositol 1,4,5-trisphosphate) receptors; thrombosis